Caesarean Delivery and Subsequent Stillbirth or Miscarriage: Systematic Review and Meta-Analysis - O’Neill, Sinéad M. (Public Library of Science, 2013)
OBJECTIVE: To compare the risk of stillbirth and miscarriage in a subsequent pregnancy in women with a previous Caesarean or vaginal delivery. DESIGN: Systematic review of the published literature including seven databases: CINAHL; the Cochrane library; Embase; Medline; PubMed; SCOPUS and Web of Knowledge from 1945 until November 11(th) 2011, using a detailed search-strategy and cross-checking of reference lists. STUDY SELECTION: Cohort, case-control and cross-sectional studies examining the association between previous Caesarean section and subsequent stillbirth or miscarriage risk. Two assessors screened titles to identify eligible studies, using a standardised data abstraction form and assessed study quality. DATA SYNTHESIS: 11 articles were included for stillbirth, totalling 1,961,829 pregnancies and 7,308 events. Eight eligible articles were included for miscarriage, totalling 147,017 pregnancies and 12,682 events. Pooled estimates across the stillbirth studies were obtained using random-effect models. Among women with a previous Caesarean an increase in odds of 1.23 [95% CI 1.08, 1.40] for stillbirth was yielded. Subgroup analyses including unexplained stillbirths yielded an OR of 1.47 [95% CI 1.20, 1.80], an OR of 2.11 [95% CI 1.16, 3.84] for explained stillbirths and an OR of 1.27 [95% CI 0.95, 1.70] for antepartum stillbirths. Only one study reported adjusted estimates in the miscarriage review, therefore results are presented individually. CONCLUSIONS: Given the recent revision of the National Institute for Health and Clinical Excellence guidelines (NICE), providing women the right to request a Caesarean, it is essential to establish whether mode of delivery has an association with subsequent risk of stillbirth or miscarriage. Overall, compared to vaginal delivery, the pooled estimates suggest that Caesarean delivery may increase the risk of stillbirth by 23%. Results for the miscarriage review were inconsistent and lack of adjustment for confounding was a major limitation. Higher methodological quality research is required to reliably assess the risk of miscarriage in subsequent pregnancies.